2008
DOI: 10.1021/cg701067r
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Light Scattering in Protein Crystallization Droplets: Adaptations for Analysis and Optimization of Crystallization Processes

Abstract: A combined imaging and dynamic light scattering (DLS) system has been developed for routine measurements in droplets in the multiwell plates used in protein crystallization. The system was tested with several standard proteins and found to be of high value for rapid identification of good crystallization conditions. A relationship between the rate of protein-aggregate-size increase and the probability of crystal formation was observed. DLS is a suitable tool for a fast optimization of the protein crystallizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 18 publications
0
41
0
1
Order By: Relevance
“…Another tool for routine analysis, scoring and optimization of the crystallization processes is dynamic light scattering (DLS). It has been demonstrated that the rate of the particle size growth is a good predictor of the outcome for the crystallization experiment and allows to assess the probability of obtaining macromolecule crystals before their growth starts [234]. In the evaluation of the crystallization trials it is also possible to utilize the fluorescence of tryptophan residues under UV light.…”
Section: Real-time Monitoring Of Crystalsmentioning
confidence: 99%
“…Another tool for routine analysis, scoring and optimization of the crystallization processes is dynamic light scattering (DLS). It has been demonstrated that the rate of the particle size growth is a good predictor of the outcome for the crystallization experiment and allows to assess the probability of obtaining macromolecule crystals before their growth starts [234]. In the evaluation of the crystallization trials it is also possible to utilize the fluorescence of tryptophan residues under UV light.…”
Section: Real-time Monitoring Of Crystalsmentioning
confidence: 99%
“…The inset in d shows a selected magnification such as Ca 2+ and Mg 2+ at concentration of 10 mM, were determined by DLS. The DLS system (SPECTROLIGHTâ„¢ 600, Xtal Concepts, Hamburg, Germany) was also used to monitor self-assembly in a corresponding 3 mg mL −1 solution after addition of different bivalent cations in situ (Dierks et al 2008). All DLS measurements were carried out at room temperature and evaluated using the provided software.…”
Section: Methodsmentioning
confidence: 99%
“…The reservoirs were filled with 35 µL protein buffer (20 mM MOPS, pH 8, 1% beta-OG) and the plate was sealed with SmartSeal (Greiner Bio-One GmbH, Germany) to avoid evaporation during the measurements. DLS measurements within these droplets were carried out at 20°C using a Spectro Light 500 instrument (XtalConcepts GmbH, Germany), a plate reader for UV/visible-imaging and in situ DLS [52]. Data were analyzed using Spectro (Nabitec GmbH, Germany).…”
Section: Methodsmentioning
confidence: 99%